PARIWISATA BERKELANJUTAN: MENGEMBANGKAN EKONOMI LOKAL TANPA MERUSAK LINGKUNGAN - Daya Pintaruan; Rosalina Kumalati; Ellyn Normelani (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2024)
Sustainable tourism has become an essential approach in Indonesia to balance economic growth with environmental and cultural conservation. This model focuses on fostering local economies by empowering communities, creating jobs, and stimulating community-led small and medium-sized enterprises (SMEs). Simultaneously, it ensures environmental protection through responsible resource management practices and cultural preservation by promoting authentic interactions and respect for local traditions. Various case studies in Indonesia, such as Pujon Kidul Tourism Village in Malang and Penglipuran Village in Bali, demonstrate that tourism can be a positive force that drives prosperity without sacrificing ecological and social integrity. This approach proves that sustainability is not just an ideal, but also an effective strategy for building a resilient and long-term beneficial tourism sector.